VD_FINDINFO Arrêt / 2016 / 524 vom 7. Juni 2016 - VD Tribunal cantonal (2016)
HOSPITALISATION EXTRA-CANTONALE | 39 al. 1 LAMal, 39 al. 1 let. d LAMal, 39 al. 1 let. e LAMal, 41 al. 1bis LAMal, 41 al. 2 LAMal, 49 al. 1 LAMal